2018
DOI: 10.1186/s12917-018-1469-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the virulence of three H3N2 canine influenza virus isolates from Korea and China in mouse and Guinea pig models

Abstract: BackgroundAvian-origin H3N2 canine influenza virus (CIV) has been the most common subtype in Korea and China since 2007. Here, we compared the pathogenicity and transmissibility of three H3N2 CIV strains [Chinese CIV (JS/10), Korean CIV (KR/07), and Korean recombinant CIV between the classic H3N2 CIV and the pandemic H1N1 virus (MV/12)] in BALB/c mouse and guinea pig models. The pandemic H1N1 (CA/09) strain served as the control.ResultsBALB/c mice infected with H1N1 had high mortality and obvious body weight l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(72 reference statements)
2
4
0
Order By: Relevance
“…JS10 has naturally occurring two amino acid (2‐aa) insertions at the distal end of the neuraminidase (NA) stalk. Consistent with previous studies, the long stalk strain showed more severe pathologic damage in mice and guinea pigs (Xie et al, ). However, no significant difference in cellular uptake between KR07 and JS10 was observed in this study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…JS10 has naturally occurring two amino acid (2‐aa) insertions at the distal end of the neuraminidase (NA) stalk. Consistent with previous studies, the long stalk strain showed more severe pathologic damage in mice and guinea pigs (Xie et al, ). However, no significant difference in cellular uptake between KR07 and JS10 was observed in this study.…”
Section: Discussionsupporting
confidence: 91%
“…For the attachment and endocytosis of influenza virus, HA initiates the recognition and attachment of receptors on target cells, albeit NA plays the role of sialidase, facilitating release of the virus during budding from the host cell, which rarely affects cellular uptake. Therefore, it may reasonably be speculated that the 2-aa insertion of NA may not contribute to the cellular uptake of canine influenza viruses, even though the long stalk strain, JS10, has higher infectivity and wider organ tropism than KR07 (Xie et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al and Dan Zhao et. al, the infected mice showed declined clinical symptoms and decreased viral load since day 5 or 7 post infection, and in our in vivo experiments, the mice were terminated at the day 5 post infection which stands for the late stage of infection (Lin et al, 2016;Xie et al, 2018). Interestingly, mycotoxins exposure also can induce pyroptosis (Li et al, 2021).…”
Section: Discussionsupporting
confidence: 50%
“…CIV was first reported in 2004, and molecular and antigenic analyses found that its genome is closely related to the equine influenza genome [11]. Although dogs are the natural host of CIV, researchers have successfully infected pigs and mice with the CIV [12,13], and researchers also isolated equine flu from pig and donkey in China [14,15], which spread across the host due to the high variability of influenza viruses. Therefore, further studies of canine innate immune response are important to control the spread of the virus.…”
Section: Introductionmentioning
confidence: 99%